Apostolides v. Orams and Another; Orams and Another v. Apostolides ([2010] EWCA Civ 9 and Case C-420/07). (2014) - Unknown
Abstract : 443 States — Recognition — Republic of Cyprus — Turkish Republic army invading Cyprus in 1974 — Occupation of northern Cyprus — Turkish Republic of Northern Cyprus ("TRNC") declared in 1983 — Only Turkey recognizing TRNC as State — Republic of Cyprus not exercising sovereign jurisdiction over northern Cyprus — Republic of Cyprus acceding to European Union in 2004 — Article 1(1) of Protocol No 10 to Act of Accession suspending application of acquis communautaire to northern Cyprus — Dispute concerning title to land in northern Cyprus — Court in Republic of Cyprus rendering judgments on title to disputed land — Council Regulation (EC) No 44/2001 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters — Whether Cypriot judgments enforceable in United Kingdom International organizations — European Union — Member States — United Kingdom Member State — Republic of Cyprus acceding to European Union in 2004 — Council Regulation (EC) No 44/2001 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters — Scope — Republic of Cyprus not exercising sovereign jurisdiction over northern Cyprus — Article 1(1) of Protocol No 10 to Act of Accession suspending application of acquis communautaire to northern Cyprus — Dispute concerning title to land in northern Cyprus — Court in Republic of Cyprus rendering judgments on title to disputed land — Recognition and enforcement of Cypriot judgments — Whether Article 1(1) of Protocol precluding United Kingdom court from recognizing and enforcing Cypriot judgments — Preliminary ruling from Court of Justice of the European Communities — Whether United Kingdom having obligation under Community law to recognize and enforce Cypriot judgments — Article 34 of Regulation prohibiting recognition manifestly contrary to public policy — International public policy — Relevance — United Kingdom's international obligations — Whether recognition of Cypriot judgments liable to infringe fundamental principle in United Kingdom legal order — Whether Cypriot judgments enforceable in United Kingdom Relationship of international law and municipal law — United Kingdom's international obligations — United Nations Security Council Resolutions requiring respect for territorial integrity of Republic of Cyprus — Respect for courts as judicial arm of sovereign 444 State — Obligations under Treaty of Guarantee — International public policy — Whether public policy applicable in United Kingdom to which enforcement of Cypriot judgments manifestly contrary — Article 34 of Council Regulation (EC) No 44/2001 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters Treaties — Effect — Protocol No 10 to Act of Accession of Republic of Cyprus to European Union — Republic of Cyprus not exercising sovereign jurisdiction over northern Cyprus — Article 1(1) of Protocol suspending application of acquis communautaire to northern Cyprus — Council Regulation (EC) No 44/2001 — Applicability — Recognition and enforcement of Cypriot judgments — The law of England